Predicting Communicative Behavior of Higher Institutions Employees during COVID-19 Pandemic: A Conceptual Assessment - Adamu Abbas Adamu; Bahtiar Mohamad; Kinkin Yuliaty Subarsa Putri (Journal of Digital Marketing and Communication, 2021)
Over the last three decades, a series of research has revealed how strategic communication may have a profound effect on how members of society behave. More precisely, communication theories have documented the media's ability to determine the agenda in society. The situational theory of problem-solving is particularly interesting because it explains why and how individual members of society communicate during a problematic situation. This hypothesis has been evaluated in a variety of contexts to determine its efficacy. However, few studies have been conducted to examine the influence of communication from corporations or governments to community members. The character of persons, particularly employees' information seeking and sharing behavior, has been significantly overlooked in the context of COVID-19. The purpose of this study is to investigate theoretically how employees to process, seek, forward, filter, choose, and exchange information regarding COVID 19.